ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (STUDI PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Asma Mutia; Nurhalis Nurhalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to analyze the effect of free cash flow, profitability, leverage, growth rates and company size on dividend payout ratios on non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. Sampling in this study used a puposive sampling technique. The data analysis technique used is multiple linear regression. The results of this study indicate free cash flow, and company size has a positive and significant effect on dividend payout ratio. Profitability, leverage, and growth rates have a negative and significant effect on the dividend payout ratio. Simultaneously free cash flow, profitability, leverage, growth rate, and company size show a significant effect on dividend payout ratio.